Reward and punishment model for elementary students’ character building in the digital era - Muhammad Arzy; Saihan Saihan; Mukaffan Mukaffan (Inovasi Kurikulum, 2025)
The digital era presents new challenges in the field of education, particularly in shaping students' character. Reward and punishment are among the strategies used to develop student behavior in line with positive values. This study aims to analyze the use of reward and punishment in shaping the character of elementary school students in the digital era. The research approach employed is a qualitative case study design. Data collection techniques include observation, interviews, and documentation. The data obtained were analyzed through three steps: data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The results of the study indicate that implementing appropriate rewards can increase students’ learning motivation and positive behavior, while educational punishment can reduce negative behavior without causing harmful psychological effects. The conclusion of this study emphasizes that a proportionally applied reward and punishment model, aligned with technological advancements, can be an effective strategy for shaping the character of elementary school students in the digital era. The implication of this research is the need for educational policies that are adaptable to digital developments, allowing the reward and punishment model to be implemented optimally.   Abstrak Era digital membawa tantangan baru dalam dunia pendidikan, terutama dalam pembentukan karakter peserta didik. Reward dan punishment menjadi salah satu strategi yang digunakan untuk membentuk perilaku peserta didik agar sesuai dengan nilai-nilai positif. Penelitian ini bertujuan untuk menganalisis reward dan punishment dalam membentuk karakter peserta didik Sekolah Dasar (SD) di era digital. Pendekatan penelitian yang digunakan adalah pendekatan kualitatif dengan desain studi kasus. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Data yang diperoleh dianalisis menggunakan tiga langkah yaitu kondensasi data, penyajian data, dan penarikan kesimpulan. Keabsahan data menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa pemberian reward yang tepat dapat meningkatkan motivasi belajar dan perilaku positif peserta didik, sedangkan punishment yang bersifat edukatif dapat mengurangi perilaku negatif tanpa menimbulkan efek psikologis yang merugikan. Kesimpulan dari penelitian ini menegaskan bahwa model reward dan punishment yang diterapkan secara proporsional dan sesuai dengan perkembangan teknologi dapat menjadi strategi efektif dalam membentuk karakter peserta didik sekolah dasar di era digital. Implikasi dari penelitian ini adalah perlunya kebijakan pendidikan yang adaptif terhadap perkembangan digital agar model reward dan punishment dapat diterapkan secara optimal. Kata Kunci: era digital; pembentukan karakter; punishment; reward; sekolah dasar